This Movement Will Take You So High and So Low - Dawson, Mia Karisa (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
I address this letter to myself on November 25, 2014, the day after the non-indictment of Michael Brown’s murderer, when a resounding silence in my college physics class sparked a fire in me and a journey of awakening and action. Somewhere between a love letter and a condolence, a reassurance and a forewarning, these words serve to soften my stumble towards empowerment and insight as I grow as a young organizer in the Black Lives Matter movement.